2014
DOI: 10.1186/1471-2261-14-58
|View full text |Cite
|
Sign up to set email alerts
|

Transfers to metropolitan hospitals and coronary angiography for rural Aboriginal and non‐Aboriginal patients with acute ischaemic heart disease in Western Australia

Abstract: BackgroundAboriginal people have a disproportionately higher incidence rate of ischaemic heart disease (IHD) than non-Aboriginal people. The findings on Aboriginal disparity in receiving coronary artery procedures are inconclusive. We describe the profile and transfers of IHD patients admitted to rural hospitals as emergency admissions and investigate determinants of transfers and coronary angiography.MethodsPerson-linked hospital and mortality records were used to identify 28-day survivors of IHD events comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
12
1
Order By: Relevance
“…An inter‐hospital transfer rate of 25% has been reported in an acute myocardial infarction cohort, which is lower than our rate of 30.2%, and this might reflect the complexity and scarcity of tertiary level renal care in rural areas . Other work studying indigenous populations has also demonstrated that inter‐hospital transfers are an integral part of the care of rural patients . Future work should examine causes for inter‐hospital transfers and the effect of greater provision of dialysis services and nephrologists in rural areas upon outcomes such as inter‐hospital transfer and mortality.…”
Section: Discussioncontrasting
confidence: 73%
“…An inter‐hospital transfer rate of 25% has been reported in an acute myocardial infarction cohort, which is lower than our rate of 30.2%, and this might reflect the complexity and scarcity of tertiary level renal care in rural areas . Other work studying indigenous populations has also demonstrated that inter‐hospital transfers are an integral part of the care of rural patients . Future work should examine causes for inter‐hospital transfers and the effect of greater provision of dialysis services and nephrologists in rural areas upon outcomes such as inter‐hospital transfer and mortality.…”
Section: Discussioncontrasting
confidence: 73%
“…That is, the team was aware from the start that localised, small-scale research identifying local, practical and targeted correctives may be more likely to give rise to change than statewide research recommending broader health system reform. Additionally, stakeholders’ awareness of the fact that other audits 51 , 52 and the statewide administrative data analysed by BAHHWA researchers had found similar disparities in treatment 15 gave the audit results increased legitimacy, and in raising a wider, systemic problem for which solutions were evident, enabled the hospital to be a leader of reform. Having strong data to prompt change within hospital settings was also identified as important in the supplementary interviews: the sort of thing you can really almost shock people with, because they do realise it’s an issue, but they might not realise the magnitude of the problem … we certainly have to drive them with the data [until they] have an interest in their health service performing better.…”
Section: Resultsmentioning
confidence: 99%
“…The Bettering Aboriginal heart health in Western Australia (BAHHWA) project investigates the ways in which the health system, multiple comorbidities, socio-economic factors and cultural differences interact to perpetuate poor health outcomes for Aboriginal Western Australians. Different aspects of the research have investigated frequency and outcomes of cardiovascular disease (CVD), the kind of care Aboriginal patients receive compared with non-Aboriginal patients, the experiences of Aboriginal people receiving care for CVD 3 , 12 15 and enablers and barriers in health system change. 16 Investigation of strategies that facilitate or impede KT is a core component of the project.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we did not adjust for confounders such as remoteness and Indigenous status, which may influence transfer and readmission patterns. 6 24 The complex pattern of counts and ratios we presented is from WA for 2000–2013 and may not be generalisable to other jurisdictions (because of different healthcare systems) or beyond the study period; however, the methods we described are generalisable to other states and territories.…”
Section: Discussionmentioning
confidence: 96%
“…These specialised coronary care services are generally located at major population centres, and many patients, especially those from non-urban areas, are transferred to one of these hospitals for treatment and management of their condition. 6 In addition, a significant number of patients with MI are readmitted for complications post-MI (such as repeat MI or heart failure), for elective procedures (such as coronary artery revascularisation or electrophysiological investigation), and to a lesser degree, for non-cardiac-related admissions. 7 8 …”
Section: Introductionmentioning
confidence: 99%